Expression, purification, and structural analysis of intracellular C-termini from metabotropic glutamate receptors - Seebahn, Angela; Sticht, Heinrich; Enz, Ralf (Methods in Enzymology, 2013)
Glutamate is the most important excitatory neurotransmitter in the mammalian central nervous system (CNS). Metabotropic glutamate receptors (mGluRs) are G-protein-coupled receptors (GPCRs) that guide several intracellular signal cascades thereby controlling multiple physiological tasks, such as neuronal excitability, learning, and memory. Consequently, these receptors are discussed in the context of several CNS-associated diseases, including addiction for drugs, Alzheimer's disease, Fragile X syndrome, night blindness, or schizophrenia. Although increasing structural information is available for the extracellular and transmembrane domains of GPCRs, data describing the nature of intracellular receptor domains are largely missing. Indeed, in all available crystal structures of neurotransmitter receptors, their intracellular domains were omitted. Most intracellular mGluR C-termini are alternatively spliced and contain multiple binding sites for interacting proteins. Therefore, analyzing their structure can identify molecular mechanisms of receptor regulation. Recently, we analyzed the conformation of the intracellular C-termini of mGluR6, mGluR7a, and mGluR8a. Here, we describe an array of biochemical, biophysical, and computational techniques suited to elucidate the nature of these highly interesting receptor domains.
EVALuna2:4686

Functional implications of novel human acid sphingomyelinase splice variants - Rhein, Cosima; Tripal, Philipp; Seebahn, Angela; Konrad, Alice; Kramer, Marcel; Nagel, Christine; Kemper, Jonas; Bode, Jens; Mühle, Christiane; Gulbins, Erich; Reichel, Martin; Becker, Cord-Michael; et al. (PLoS ONE, 2012)
Acid sphingomyelinase (ASM) hydrolyses sphingomyelin and generates the lipid messenger ceramide, which mediates a variety of stress-related cellular processes. The pathological effects of dysregulated ASM activity are evident in several human diseases and indicate an important functional role for ASM regulation. We investigated alternative splicing as a possible mechanism for regulating cellular ASM activity.We identified three novel ASM splice variants in human cells, termed ASM-5, -6 and -7, which lack portions of the catalytic- and/or carboxy-terminal domains in comparison to full-length ASM-1. Differential expression patterns in primary blood cells indicated that ASM splicing might be subject to regulatory processes. The newly identified ASM splice variants were catalytically inactive in biochemical in vitro assays, but they decreased the relative cellular ceramide content in overexpression studies and exerted a dominant-negative effect on ASM activity in physiological cell models.These findings indicate that alternative splicing of ASM is of functional significance for the cellular stress response, possibly representing a mechanism for maintaining constant levels of cellular ASM enzyme activity.
EVALuna2:4672

Modulation of TTX-sensitive voltage-dependent Na+ channels by ?-bungarotoxin in rat cerebellar neurons - Guo, Da; Xiang, Wei; Seebahn, Angela; Becker, Cord-Michael; Strauss, Olaf (BMC Neuroscience, 2012)
The modulation of voltage-dependent Na+ channels by lipid metabolites such as arachidonic acid or eicosanoids plays a role in physiological functions as well as in degenerative diseases. So far TTX-resistant channels were found mainly to be regulated by lipid metabolites.We investigated the lipid-dependent modulation of TTX-sensitive (TTX-s) Na+ channels using ?-bungarotoxin (?-BuTX, 10 pM), which has an intrinsic phospholipase-A2 activity, and indomethacin (10 ?M), which blocks cyclooxygenase activity in primary cerebellar neurons. To investigate TTX-s Na+ channels, whole-currents were measured under K+-free conditions and blocked by 10 nM TTX. The currents resulting from calculating the difference of currents measured in the presence and the absence of TTX were used for further analysis. Application of indomethacin mainly changed the current kinetics but has only minor effects on voltage-dependence. In contrast ?-BuTX increased the maximal current amplitude and shifted the voltage-dependent activation towards more negative potentials. The effects of ?-BuTX were blocked by indomethacin. Analysis of lipid metabolites which accumulate by treatment with ?-BuTX using MALDI-TOF MS showed an increase of cyclooxygenase reaction products in relation to arachidonic acid.In summary, we conclude that TTX-sensitive Na+ channels can be directly modulated by cyclooxygenase reaction products leading to higher activity at less depolarized potentials and subsequent higher excitability of neurons. Since activation of cyclooxygenase is also involved in pathways leading to apoptotic cells death this could play a role in degenerative diseases of the CNS and highlights a possible protective effect of cyclooxygenase inhibition.
EVALuna2:4677

Oxidative stress-induced posttranslational modifications of human hemoglobin in erythrocytes - Xiang, Wei; Weisbach, Volker Günter; Sticht, Heinrich; Seebahn, Angela; Bussmann, Julia; Zimmermann, Robert; Becker, Cord-Michael (Archives of Biochemistry and Biophysics, 2013)
Posttranslational modifications (PTMs) have been reported in hemoglobin (Hb) treated with ROS/RNS in cell-free experiments. However, little is known about oxidative PTMs of Hb occurring within the erythrocytes. The aim of this study is to characterize the patterns of Hb PTMs in erythrocytes under oxidative stress. Using mass spectrometry, we investigated specifically methionine/tryptophan oxidation, tyrosine nitration, and the modification via 4-hydroxynonenal (HNE), a product of lipid-peroxidation, on Hb. We demonstrated that the treatment with H(2)O(2)/nitrite induced higher levels of Hb oxidation/nitration in purified Hb preparations than in unpurified hemolysates and erythrocytes, indicating that ROS/RNS are primarily removed by antioxidative mechanisms. We further studied Hb from erythrocytes exposed to ?-irradiation. An irradiation of 30-100 Gy triggered a remarkable increase of intracellular ROS. However, 30 Gy did not induce apparent changes in Hb oxidation/nitration and hemolysis, while Hb oxidation/nitration and hemolysis were significantly enhanced by 100 Gy, suggesting that Hb oxidation/nitration are the consequence of overwhelmed antioxidative mechanisms after oxidative attack and reflect the severity of the oxidative damage of erythrocytes. Although irradiation was known to induce lipid-peroxidation, we could not detect HNE-Hb adducts in irradiated erythrocytes. Analyzing PTM patterns suggests Hb nitration as a more suitable indicator of the oxidative damage of erythrocytes.
EVALuna2:4676

Peptide labeling with photoactivatable trifunctional cadaverine derivative and identification of interacting partners by biotin transfer - App, Christine; Knop, Jana; Huff, Thomas; Seebahn, Angela; Becker, Cord-Michael; Iavarone, Federica; Castagnola, Massimo; Hannappel, Ewald (Analytical Biochemistry, 2014)
A new photoactivatable trifunctional cross-linker, cBED (cadaverine-2-[6-(biotinamido)-2-(p-azidobenzamido) hexanoamido]ethyl-1,3'-dithiopropionate), was synthesized by chemical conversion of sulfo-SBED (sulfosuccinimidyl-2-[6-(biotinamido)-2-(p-azidobenzamido) hexanoamido]ethyl-1,3'-dithiopropionate) with cadaverine. This cross-linker was purified by reversed-phase high-performance liquid chromatography (RP-HPLC) and characterized using matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) analysis. cBED is based on sulfo-SBED that has a photoactivatable azido group, a cleavable disulfide bond for label transfer methods, and a biotin moiety for highly sensitive biotin/avidin detection. By ultraviolet (UV) light, the azido group is converted to a reactive nitrene, transforming transient bindings of interacting structures to covalent bonds. In contrast to the sulfo-N-hydroxysuccinimide (sulfo-NHS) moiety of sulfo-SBED, which attaches quite unspecifically to amino groups, cBED includes a cadaverine moiety that can be attached by transglutaminase more specifically to certain glutamine residues. For instance, thymosin ?4 can be labeled with cBED using tissue transglutaminase. By high-resolution HPLC/ESI-MS (electrospray ionization-mass spectrometry) and tandem MS (MS/MS) of the trypsin digest, it was established that glutamine residues at positions 23 and 36 were labeled, whereas Q39 showed no reactivity. The covalent binding of cBED to thymosin ?4 did not influence its G-actin sequestering activity, and the complex could be used to identify new interaction partners. Therefore, cBED can be used to better understand the multifunctional role of thymosin ?4 as well as of other proteins and peptides.
EVALuna2:4695

Prosequence switching: an effective strategy to produce biologically active E. coli heat-stable enterotoxin STh - Weiglmeier, Philipp R.; Berkner, Hanna; Seebahn, Angela; Vogel, Nicolas; Schreiber, Rainer; Woehrl, Birgitta M.; Schwarzinger, Stephan; Roesch, Paul (Journal of Biomolecular Structure & Dynamics, 2014)
Enterotoxigenic Escherichia coli (ETEC) infections account for the majority of cases of acute secretory diarrhea. The causative agents are enterotoxins secreted by ETEC, among them is the heat-stable enterotoxin, STh. STh is a 19-amino acid peptide containing three disulfide bonds that stimulates fluid secretion in the bowel by binding to the receptor domain of intestinal guanylyl cyclase C (GC-C). Since GC-C agonists have pharmacologic potential for diagnosis and treatment of disorders such as constipation-predominant irritable bowel syndrome (IBS-C), chronic constipation, and colorectal carcinoma, it is crucial to develop methods for the large-scale production of STh and related peptides. Here, we present a strategy for recombinant expression of STh that relies on the use of the prosequence of human uroguanylin to support proper folding and disulfide bond formation. The chimeric protein CysCys-STh consisting of the propeptide of uroguanylin as N-terminus and the STh peptide as C-terminus was expressed in E. coli, and an efficient purification protocol was developed. Trypsin digestion of this protein released the enterotoxin which could be obtained in high purity. NMR and mass spectrometry confirmed the identity and homogeneity of the toxin, and its biological activity was confirmed by a cell-based in vivo assay. The expression scheme introduced here represents a cost-efficient and scalable way of STh production.
EVALuna2:4705

RanBPM is expressed in synaptic layers of the mammalian retina and binds to metabotropic glutamate receptors. - Seebahn, Angela; Rose, Melanie; Enz, Ralf (FEBS letters, 2008)
In the central nervous system, synaptic signal transduction depends on the regulation of neurotransmitter receptors by interacting proteins. Here, we searched for proteins interacting with two metabotropic glutamate receptor type 8 isoforms (mGlu8a and mGlu8b) and identified RanBPM. RanBPM is expressed in several brain regions, including the retina. There, RanBPM is restricted to the inner plexiform layer where it co-localizes with the mGlu8b isoform and processes of cholinergic amacrine cells expressing mGlu2 receptors. RanBPM interacts with mGlu2 and other group II and group III receptors, except mGlu6. Our data suggest that RanBPM might be associated with mGlu receptors at synaptic sites. © 2008 Federation of European Biochemical Societies.
UnivIS-Import:2017-12-18:Pub.2008.med.IB.profes_1.ranbpm
Keywords: mGlu2; mGlu8b; Protein interaction; RanBP9; RanBPM; Retina

Structural characterization of intracellular C-terminal domains of group III metabotropic glutamate receptors. - Seebahn, Angela; Dinkel, Holger; Mohrlüder, J.; Hartmann, Rainer; Vogel, N.; Becker, Cord-Michael; Sticht, Heinrich; Enz, Ralf (Febs Letters, 2011)
Metabotropic glutamate receptors (mGluRs) are regulated by interacting proteins that mostly bind to their intracellular C-termini. Here, we investigated if mGluR6, mGluR7a and mGluR8a C-termini form predefined binding surfaces or if they were rather unstructured. Limited tryptic digest of purified peptides argued against the formation of stable globular folds. Circular dichroism, 1H NMR and 1H 15N HSQC spectra indicated the absence of rigid secondary structure elements. Furthermore, we localized short linear binding motifs in the unstructured receptor domains. Our data provide evidence that protein interactions of the analyzed mGluR C-termini are mediated rather by short linear motifs than by preformed folds. © 2011 Federation of European Biochemical Societies. Published by Elsevier B.V. All rights reserved.
UnivIS-Import:2015-04-14:Pub.2011.med.IB.profes_1.struct
Keywords: G-protein coupled receptor; Metabotropic glutamate receptor; Neurotransmitter receptor; Short linear motif